2018
DOI: 10.1097/01.aoa.0000529983.77883.af
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Versus Placebo in Pregnancies at High Risk for Preterm Preeclampsia

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…18 24 However, another controlled trial showed a reduction in preterm preeclampsia in patients that used aspirin. 25 Our patients, guided by the institution protocol, used aspirin prophylaxis throughout the pregnancy, as well as calcium supplementation, as this is recommended in some groups of patients such as those with SLE. 26…”
Section: Discussionmentioning
confidence: 99%
“…18 24 However, another controlled trial showed a reduction in preterm preeclampsia in patients that used aspirin. 25 Our patients, guided by the institution protocol, used aspirin prophylaxis throughout the pregnancy, as well as calcium supplementation, as this is recommended in some groups of patients such as those with SLE. 26…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The ASPRE trial did not find a significant difference in sPTB in the aspirin vs the placebo group. 12 Nevertheless, the results of an individual participant data meta-analysis including 17 RCT and 28,797 women showed a lower risk of sPTB at less than 37 weeks (RR 0.93, 95% CI 0.86-0.996) and less than 34 weeks (RR 0.86, 95% CI 0.76-0.99) in women assigned to antiplatelet treatment compared with placebo or no treatment. 14 On the basis of this finding, the authors suggested that prophylactic treatment with low-dose aspirin might be applied to a broader population of pregnant women other than those with a high risk of placental dysfunction.…”
Section: Women Who Delivered Spontaneously Preterm Had Lower Papp-a M...mentioning
confidence: 97%
“…8,9 Similarly, an imbalance in angiogenic factors with increased antiangiogenic elements such as soluble endoglin (sEng) and soluble fms-like tyrosine kinase receptor-1 (sFlt-1) has also been associated with sPTB and early-term birth. 10,11 The ASPRE study introduced a first-trimester screening algorithm for preterm PE that combines maternal cardiovascular and placental factors to recognise women at higher risk of early uteroplacental dysfunction 12 . A subsequent clinical-effectiveness study demonstrated that the prophylactic treatment with low-dose aspirin in women at high risk of preterm PE could reduce the incidence of preterm PE by 80%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of a screening test with aspirin prophylaxis started before 16 GW can reduce the risk of PE before 37 GW by 62 % 17 .…”
Section: Integrating Doppler Ultrasound Into Obstetrics Managementmentioning
confidence: 99%